High protein diet in pregnancy.Effects on neonatal metabolism (Revista Española de Fisiología, 1986)
The effect of a high protein diet (20% casein + D,L-methionine) administered to Wistar rats during pregnancy on some aspects of cellular growth and RNA metabolism of progeny has been studied.Comparisons were made with well-nourished (10% casein + D,L-methionine) controls.Newborns individual weight, litter weight and number of newborns per litter were unmodified.However, neonate protein content dropped significantly when compared with controls.Both rate of DNA and number of nuclei were unchanged.Protein/DNA ratio (cellular size relative to protein) decreased, which might have led to an atrophy phenomenon, even if the newborn weight/number of nuclei ratio was not modified.Acid DNase activity rose, bringing about DNA breakdown.Total RNA content together with RNase activity fell in newborn from rats suffering high protein diet.Moreover, protein synthesis capacity (RNA/protein ratio) did not change.These results suggest that the administration of a high protein diet to pregnant rats lead to changes in newborn protein rate and nucleic acid turnover by modulating specific nuclease activity.